China's spatial (dis)integration as a multiethnic paradox: what do the interprovincial data say? - Rongxing Guo (China Finance and Economic Review, 2016)
Background: Compared with its surging foreign trade, China's domestic trade growth from 2000 to 2010 had been less encouraging. Then, what are the driving forces behind the dynamic pattern of China's domestic trade? Methods: Using the gravity model of trade and China's interprovincial panel data, this paper shows that the negative effect of distance-related transactions costs on interprovincial trade tends to rise from 2000 to 2010. After constructing China's 56 ethnic groups into a single, interprovincial similarity index, I cannot find any evidence that supports the view that ethnic links should serve as a factor promoting bilateral trade. Results: However, my estimated coefficients on 37 major ethnic groups show that both positive and negative ethnic influences on trade exist in China. Specifically, 14 ethnic groups (Lahu, Qiang, Jingpo, Tu, Mongol,Manchu, Hui, Zhuang, Dongxiang, Daur, Kirgiz, She, Maonan, and Tibetan) are found to contribute to China's interprovincial trade, while five ethnic groups (Han, Va, Kazak, Dai, and Blang) tend to impede China's interprovincial trade. Conclusions: These findingswill be useful for policy-makers to reappraise which of China's ethnic groups are playing the most (least) important roles in, and to introduce the optimal informal institutions into, the promotion of interprovincial economic cooperation in China.
Keywords: 330; Domestic trade; Spatial (dis)integration; Interprovincial ethnic linkage; Province; China